2016
DOI: 10.1111/age.12456
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide association study reveals novel variants for growth and egg traits in Dongxiang blue‐shelled and White Leghorn chickens

Abstract: The Dongxiang Blue-shelled chicken is one of the most valuable Chinese indigenous poultry breeds. However, compared to the Italian native White Leghorn, although this Chinese breed possesses numerous favorable characteristics, it also exhibits lower growth performance and fertility. Here, we utilized genotyping sequencing data obtained via genome reduction on a sequencing platform to detect 100,114 single nucleotide polymorphisms and perform further biological analysis and functional annotation. We employed cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 56 publications
2
19
0
Order By: Relevance
“…ELL and ARL8A. Note that the first is among the prioritized candidates (ranked 8th) while the second ARL8A (ADP ribosylation factor like GTPase 8A) has been associated with eggshell thickness and eggshell formation [5] in chickens.…”
Section: Functional Candidate Genesmentioning
confidence: 99%
See 1 more Smart Citation
“…ELL and ARL8A. Note that the first is among the prioritized candidates (ranked 8th) while the second ARL8A (ADP ribosylation factor like GTPase 8A) has been associated with eggshell thickness and eggshell formation [5] in chickens.…”
Section: Functional Candidate Genesmentioning
confidence: 99%
“…High-density SNP (single nucleotide polymorphism) genotyping arrays have greatly facilitated the detection of candidate causal variants in genome-wide association studies (GWAS) for various traits related to egg production and egg quality. Most GWAS have, so far, focused on the detection of additive SNPs for egg production [5][6][7] and egg quality traits [5,[7][8][9][10]. It is noted that these studies have been focusing on EN in layer chickens and not broiler breeders.…”
Section: Introductionmentioning
confidence: 99%
“…It is well-known that EW is a highly heritable quantitative trait (Savegnago et al, 2011 ; Yi et al, 2014 ). Thus, in concert with developments in molecular genetics, research has been carried out to elucidate the genetic basis of EW (Schreiweis et al, 2006 ; Wright et al, 2006 ; Liu et al, 2011 ; Wolc et al, 2012 , 2014 ; Yi et al, 2015 ; Liao et al, 2016 ); a total of 248 quantitative trait loci (QTLs) on 19 different chromosomes (18 autosomes and one sex chromosome) have been reported to be associated with EW and are listed in the AnimalQTLdatabase ( https://www.animalgenome.org/cgi-bin/QTLdb/index ). However, despite a range of studies in this area, wide confidence intervals for the positions of QTL remain that have rarely been replicated.…”
Section: Introductionmentioning
confidence: 99%
“…Yuan et al (2015) detected nine genome-wide loci that significantly affected egg number during the laying phases of 21-26, 27-36, and 37-72 weeks using GWAS technology. Liao et al (2016) found a genome-wide significant locus (ss1985401199) located on the sex chromosome Z, which was associated with egg number in hens at 25-45 weeks. In the present study, six SNPs were significantly associated with ENA300 (4) and EN462 (2).…”
Section: Egg Numbermentioning
confidence: 97%
“…Tuiskula-Haavisto et al (2002) found that a region related to egg weight at 40 weeks was located on chromosome 4. Liao et al (2016) discovered an SNP (ss1985401190) located on GGA4, which was significantly associated with EW. In the present study, six SNPs were significantly associated with FEW (1), EW300 (3), and EW462 (2), two of which were mapped to chromosome 4.…”
Section: Egg Numbermentioning
confidence: 99%